Population Pharmacokinetics of Dapoxetine in Healthy Chinese Male Subjects. - Pu, Libin; Wu, Tong; Bai, Fuqiang; Lu, Haobo; Wang, Yiming; Gao, Yuan; Qiu, Wen (Journal of Clinical Pharmacology, 2026)
Dapoxetine is a short‐acting selective serotonin reuptake inhibitor used to treat premature ejaculation. However, its clinical effectiveness is challenged by substantial inter‐individual variability in pharmacokinetics, as both the drug's therapeutic efficacy and the incidence of adverse reactions are highly dependent on its exposure. This study aims to develop a population pharmacokinetic model for dapoxetine, to investigate the sources of the variability, and to identify demographic and pharmacogenetic factors that influence drug exposure. The pharmacokinetic data for this analysis were obtained from a bioequivalence study conducted in 39 healthy Chinese male subjects. As part of this study, all volunteers were genotyped for the CYP3A4*1G, CYP3A5*3, CYP2D6*10, and CYP2D6*41 allelic variants. Population pharmacokinetic modeling was performed in Monolix. The final model was then used to simulate and compare the effect of different covariate levels on dapoxetine exposure. A two‐compartment model with first‐order absorption and an absorption lag time best described the pharmacokinetics of dapoxetine. The population parameters for apparent clearance (CL/F), apparent intercompartmental clearance (Q/F), apparent central volume of distribution (Vc/F), apparent peripheral volume of distribution (Vp/F), absorption lag time (Tlag), and absorption rate constant (ka) were 37.8 L/h, 17.2 L/h, 65.6 L, 191.7 L, 0.68 h, and 1.29/h, respectively. CYP2D6*10 and CYP2D6*41 alleles were found to be significant covariates on CL/F. The CYP3A4*1G allele influenced Q/F, while body mass index (BMI) was a significant covariate on Vc/F. Our analysis identified CYP2D6*10 and CYP2D6*41 polymorphisms as the significant factors contributing to inter‐individual variability and influencing drug exposure.